Experimental estimates of hygroscopic growth of particulate fission product species (mixed CsI–CsOH) with implications in reactor accident safety research. (June 2022) - Mariam,; Joshi, Manish; Khan, Arshad; Mishra, Gaurav; Tripathi, S.N.; Sapra, B.K.
Abstract: Studies on severe nuclear reactor accidents consider CsI and CsOH as the two predominant forms of cesium expected to be released following a reactor accident; 137 Cs, 134 Cs and 131 I being their dominant radioactive forms. Recent studies have measured the hygroscopic growth factors (HGF) and activation fractions for laboratory generated CsI and CsOH particles in sub-saturation and super-saturation relative humidity environments. This work measures and compares the HGF of mixed CsI–CsOH particles with those of individual components. The experiments have been performed with hygroscopic tandem differential mobility analyser for varying mass ratios (w/w) of CsI: CsOH and the results have been compared with the theoretical estimates made using Brechtel and Kredneweis (2000) theory in conjugation of ZSR (Zdanovskii–Stokes–Robinson) mixing rule. The study shows different behavioural pattern of hygroscopic growth of mixed particles in comparison to individual components. A clear transitional change in the growth factor patterns was observed for the ratio below 1:1. Additionally, the experiments to study the effect of different dry diameters (50, 100, 150 and 200 nm) for 1:1 ratio revealed that hygroscopic growth was independent of initial dry diameter. Effect of dehydration for 3 mixing ratios viz., 1:02, 1:1 and 1:10 showed continuous pattern indicating the dominance of CsOH. Terminal settling velocities for the mixed and individual particles are compared for highlighting the probable impact on surface deposition flux calculations. The aerosol hygroscopic growth of mixed CsI–CsOH particles has direct implications in improving source term estimates for a severe reactor accident safety analysis.